compas-dev/compas: COMPAS 1.14.1 - Tom Van Mele; Gonzalo Casas; beverlylytle; Romana Rust; Andrew Liew; Li; Anton Tetov; Rafael Pastrana; Rippmann; Juney Lee; Achilleas Xydis; Mathias Bernhard; et al. (Zenodo, 2022)
Added Added doc test step in CI/CD. Changed Fixed symlink expansion for directories relative to the COMPAS installation folder, eg. compas.DATA when used from IronPython. Fixed the result of compas.__version__ on dev installs to properly include git hash. Move data files inside the folder included in the source distribution (ie. non-dev installs). Fixed IronPython detection on ipy 2.7.12 and higher. Removed